OPTIMIZATION OF HUMAN RESOURCE MANAGEMENT IN THE CREATIVE INDUSTRY IN BANDUNG - Yani Restiani Widjaja (CV. Radja Publika, 2023)
This study discusses the optimization of human resource management in the creative industry in Bandung. The creative industry is one of the important sectors that supports economic growth, innovation, and employment opportunities. Bandung, as one of Indonesia’s creative cities, has strong potential in various creative subsectors such as fashion, culinary, design, digital media, music, and visual arts. However, the rapid development of the creative industry also creates challenges in managing human resources effectively. This study uses a qualitative descriptive method through literature review, observation, and analysis of human resource management practices in creative businesses. The results show that the optimization of human resource management is essential to improve employee productivity, creativity, innovation, and business competitiveness. Key aspects that need to be optimized include recruitment and selection, training and development, employee motivation, leadership, performance evaluation, work environment, and employee retention. Creative businesses in Bandung need to implement flexible but structured human resource management strategies to support creative talent and sustainable business growth. This study concludes that effective human resource management can strengthen the competitiveness of Bandung’s creative industry and contribute to the development of the local creative economy.